Effect of oral hygiene instruction and scaling on oral malodour in a population of Turkish children with gingival inflammation - C. KARA, A. TEZEL & R. ORBAK (Paediatric Dentistry, 2006)
Oral malodour affects a large proportion of the population, and may cause a significant social or psychological handicap to those suffering from it. The condition has a positive correlation with the accumulation of bacterial plaque in the oral cavity.